Gain-of-function KCNJ6 Mutation in a Severe Hyperkinetic Movement Disorder Phenotype. (1st August 2018) - Horvath, Gabriella A.; Zhao, Yulin; Tarailo-Graovac, Maja; Boelman, Cyrus; Gill, Harinder; Shyr, Casper; Lee, James; Blydt-Hansen, Ingrid; Drögemöller, Britt I.; Moreland, Jacqueline; Ross, Colin J.; Wasserman, Wyeth W.; et al.
Highlights: Case study of human with de novo mutation in KCNJ6 (GIRK2) Clinical findings of severe hyperkinetic movement disorder and developmental delay. Mutation near pore of GIRK2 alters G protein activation and ion selectivity. Inward depolarizing current blocked by QX-314, similar to GIRK2 weaver mutation. Screen for possible KCNJ6 mutations in patients with severe movement disorders. Abstract: Here, we describe a fourth case of a human with a de novo KCNJ6 (GIRK2) mutation, who presented with clinical findings of severe hyperkinetic movement disorder and developmental delay, similar to the Keppen–Lubinsky syndrome but without lipodystrophy. Whole-exome sequencing of the patient's DNA revealed a heterozygous de novo variant in the KCNJ6 (c.512T>G, p.Leu171Arg). We conducted in vitro functional studies to determine if this Leu-to-Arg mutation alters the function of GIRK2 channels. Heterologous expression of the mutant GIRK2 channel alone produced an aberrant basal inward current that lacked G protein activation, lost K + selectivity and gained Ca 2+ permeability. Notably, the inward current was inhibited by the Na + channel blocker QX-314, similar to the previously reported weaver mutation in murine GIRK2. Expression of a tandem dimer containing GIRK1 and GIRK2(p.Leu171Arg) did not lead to any currents, suggesting heterotetramers are not functional. In neurons expressing p.Leu171Arg GIRK2 channels, these changes in channel properties would be expected to generate a sustained depolarization, instead of the normal G protein-gated inhibitory response, which could be mitigated by expression of other GIRK subunits. The identification of the p.Leu171Arg GIRK2 mutation potentially expands the Keppen–Lubinsky syndrome phenotype to include severe dystonia and ballismus. Our study suggests screening for dominant KCNJ6 mutations in the evaluation of patients with severe movement disorders, which could provide evidence to support a causal role of KCNJ6 in neurological channelopathies.